Stress-Strain Behavior of Cementitious Materials with Different Sizes - Jikai Zhou; Pingping Qian; Xudong Chen (The Scientific World Journal)
The size dependence of flexural properties of cement mortar and concrete beams is investigated. Bazant’s size effect law and modified size effect law by Kim and Eo give a very good fit to the flexural strength of both cement mortar and concrete. As observed in the test results, a strong size effect in flexural strength is found in cement mortar than in concrete. A modification has been suggested to Li’s equation for describing the stress-strain curve of cement mortar and concrete by incorporating two different correction factors, the factors contained in the modified equation being established empirically as a function of specimen size. A comparison of the predictions of this equation with test data generated in this study shows good agreement.